Assessment of the effects of ozone exposure and plant competition on the reproductive ability of three therophytic clover species from Iberian pastures - Gimeno, B S; Bermejo, V; Sanz, J; de la Torre, D; Gil, J M (Atmospheric Environment, 2004)
Ozone (O3 ) phytototoxicity has been reported on a wide range of crops and wild Central European plant species, however no information has been provided regarding the sensitivity of plant species from dehesa Mediterranean therophytic grasslands in spite of their great plant species richness and the high O3 levels that are recorded in this area. A study was carried out in open-top chambers (OTCs) to assess the effects of O3 and competition on the reproductive ability of three clover species: Trifolium cherleri, Trifolium subterraneum and Trifolium striatum. A phytometer approach was followed, therefore plants of these species were grown in mesoscosms composed of monocultures of four plants of each species, of three plants of each species competing against a Briza maxima individual or of a single plant of each clover species competing with three B. maxima plants. Three O3 treatments were adopted: charcoal ﬁltered air (CFA), non-ﬁltered air (NFA) and non-ﬁltered air supplemented with 40 nl l 1 of O3 (NFA+). The different mesocosms were exposed to the different O3 treatments for 45 days and then they remained in the open. Ozone exposure caused reductions in the ﬂower biomass of the three clover species assessed. In the case of T. cherleri and T. subterraneum this effect was found following their exposure to the different O3 treatments during their vegetative period. An attenuation of these effects was found when the plants remained in the open. Ozone-induced detrimental effects on the seed output of T. striatum were also observed. The ﬂower biomass of the clover plants grown in monocultures was greater than when competing with one or three B. maxima individuals. An increased ﬂower biomass was found in the CFA monoculture mesocosms of T. cherleri when compared with the remaining mesocosms, once the plants were exposed in the open for 60 days. The implications of these effects on the performance of dehesa acid grasslands and for the definition of O3 critical levels is discussed
Keywords: Critical levels; Dehesa; flower biomass; mediterranean grasslands; seed production